Peningkatan Hasil Belajar Matematika Materi Volume Bangun Ruang Melalui Model Rme Berbasis Teori Bruner Pada Siswa Kelas VI SDN Sidokare 3 Sidoarjo - Purwanti Suhartini (Mathematics Department of Mathematics and Natural Sciences Unisda Lamongan, 2019)
Based on the initial test of mathematics on the building volume material in 6th students of Sidokare 3 Elementary School shows that students learning outcomes are still under the minimum of KKM score. The problem is caused by the mistakes in calculating and also they don’t understand about the formula, some students make mistakes because they less understand the basic of multiplication and division. Another factor is that the teachers used conventional method and also don’t to related the problem to the real condition, the teachers don’t used the instructional media. An alternative solution by the RME model based on Bruner’s theory. This study used a CAR design. The research subject were 32 students. The data collection techniques used test, observation, field notes and documentation. The data analyzed by qualitative and quantitative techniques. The result of this study showed that student learning outcomes in pre-cycle were 41%, cycle I was 75% and cycle II was 94%. The conclusion is the application of the RME model based on the Bruner Theory has been proven to be affective in improving student learning outcomes in 6th students of Sidokare 3 Elementary School.